Examining the components of freedom values in contemporary Chinese society - Zhang, Yue; Huang, Heshui; Tian, Jiao (Frontiers in Psychology, 2024)
This research paper explores the structure and connotation of freedom values among contemporary Chinese individuals. By considering the backdrop of Chinese society, history, and culture, a comprehensive method encompassing literature analysis, focus group interviews, in-depth interviews, and questionnaire surveys was employed. The resulting conceptual model comprises five dimensions: behavior within boundaries,independence without interference, autonomy with responsibility, rights with guarantee, and equality without domination. This model effectively unifies the consensus on freedom values among the Chinese populace, providing a framework for the dissemination and cultivation of freedom within Chinese society. The findings contribute to a deeper understanding of freedom values and offer valuable insights for scholars, policymakers, and practitioners seeking to promote freedom and societal well-being. Keywor ds ： Freedom values, Contemporary Chinese individuals, Conceptual model, Cultural context, Societal well-beingFreedom is an ancient and crucial subject within the realms of modern philosophy, politics, and communication. The pursuit of freedom as an ideology can be traced back to ancient Greek civilization. In the 17th century, Western society shaped the systematic value and political idea of freedom, laying the foundation for modern nations. This cornerstone value also resonates in China's cultural heritage, evolving through its historical transformations. The 18th National Congress of the Communist Party of China (CPC) report integrated freedom into core socialist values as the primary societal value orientation. Since then, the study of freedom values has garnered significant attention and research focus within Chinese academia.So, what exactly is freedom? Montesquieu highlighted in his book On the Spirit of the Laws